Comparison of Cumulative Live Birth Rate Between Aged PCOS Women and Controls in IVF/ICSI Cycles - Mai, Zhuoyao; Liu, Manlin; Pan, Ping; Li, Lin; Huang, Jia; Chen, Xiaoli; Yang, Dongzi (Frontiers in Endocrinology, 2021)
The present study aimed to assess whether women with polycystic ovarian syndrome (PCOS) ≥35 years age undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycles experienced a higher cumulative live birth rate (CLBR) over a two-year period compared with age- and body mass index (BMI)-matched patients with tubal factor infertility. Through propensity score matching (PSM) approach, the authors retrospectively analyzed the IVF/ICSI outcomes of 263 PCOS patients (35-46 years of age [mean, 37 years]) and 526 age- and BMI-matched tubal factor controls two years after oocyte retrieval. Multivariate regression analysis was performed to explore factors influencing cumulative live birth. Women with PCOS exhibited better ovarian reserve and response, and higher CLBR in two years compared with age- and BMI-matched controls (CLBR: 55.51% in PCOS vs. 38.02% in control, p<0.001). Multivariate logistic regression analysis revealed that the number of transferable embryos and antral follicle counts were both significant independent factors predicting cumulative live birth after adjusting for female age, female body mass index, percentage of transferred blastocysts, number of embryos transferred per embryo-transfer cycle, diagnosis of PCOS and freeze-all cycles (p<0.001, p=0.045). Women with PCOS ≥ 35 years of age demonstrated a higher CLBR over two years compared with age- and BMI-matched controls. This could be explained by favorable oocyte reserve and more available embryos compared with controls, which overcome the compromised oocyte quality in aged PCOS patients.